ANALISIS PENGARUH DIGITAL MARKETING, ORIENTASI PASAR, DAN INOVASI PRODUK HIJAU TERHADAP KINERJA PEMASARAN PADA UMKM KULINER DI KABUPATEN WONOSOBO - Ali Salobar, Aditia Lade; Efendi, Bahtiar; Maulana Akbar, Muhamad Asif (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of digital marketing, market orientation, and green product innovation on the marketing performance of culinary MSMEs in Wonosobo Regency. Digital marketing plays a crucial role for MSMEs to expand market reach and increase interaction with customers effectively. In addition, a good market orientation helps MSMEs better understand consumer needs and preferences, while green product innovation contributes to creating added value that supports sustainability principles. This study uses a quantitative approach with survey methods and multiple linear regression analysis to test the influence of these variables. Data was collected from 100 respondents who are culinary MSME actors in Wonosobo through a questionnaire that was systematically prepared. The results of the study show that digital marketing, market orientation, and green product innovation have a positive and significant influence on marketing performance. This finding is expected to provide insight for culinary MSME players in optimizing their marketing strategies through a digital approach, a deeper understanding of the market, and sustainable product innovation